2020
DOI: 10.1108/ejm-12-2017-0965
|View full text |Cite
|
Sign up to set email alerts
|

The effect of complete versus partial observations on service evaluations

Abstract: Purpose The purpose of this paper is to investigate the effect of complete versus partial observations of service failure and recovery. This study also aims at investigating the effect of observing customers’ need for cognitive closure and types of compensation that a service provider offers. Design/methodology/approach Two experiments are conducted to test the research hypotheses. The authors use scenarios describing failure and recovery encounters that occur to a target customer at restaurant settings, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…A rich literature in marketing has examined consumers' reactions to service failure (Sharifi et al, 2017;Sharifi and Spassova, 2020) and how individuals attribute blame for negative events (Abbasi, 2020;Palmeira et al, 2015). While some research has examined minority consumers (Baker et al, 2008), to the best of the authors' knowledge, no research has examined how being part of a minority influences evaluations of service failure.…”
Section: Future Researchmentioning
confidence: 99%
“…A rich literature in marketing has examined consumers' reactions to service failure (Sharifi et al, 2017;Sharifi and Spassova, 2020) and how individuals attribute blame for negative events (Abbasi, 2020;Palmeira et al, 2015). While some research has examined minority consumers (Baker et al, 2008), to the best of the authors' knowledge, no research has examined how being part of a minority influences evaluations of service failure.…”
Section: Future Researchmentioning
confidence: 99%
“… Chen (2018) also argued some mixed findings on the correlation between customer participation and the causal attribution of a particular service failure. Furthermore, several prior research efforts also showed that future studies could expand the type of failure attribution such as controllability ( Dong et al, 2008 , Roggeveen et al, 2012 , Abbasi, 2020 ). In addition, there has been a call to extend the research focus on the airline industry ( Zhang and Shao, 2018 , Abbasi, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…From a business perspective, observing customers usually outnumber the focal customers. Moreover, service incivility from the viewpoint of observers has negative implications for the firm's performance and its competitive advantage (Abbasi, 2020; Mattila et al, 2014). This is particularly more challenging, yet under‐researched, in the context of intercultural service encounters (Argo & Dahl, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, ethnically distant individuals are likely to pay different levels of attention to contextual and social factors in an intercultural social exchange (Johnson & Grier, 2013). To this extent, we study two relevant triggers of the stress–engagement mechanism, namely availability of information about the service incivility (Abbasi, 2020) and ethnic similarity, which is the observing customer's perceived congruence of ethnic backgrounds to the focal employee (Wan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation